Design and fabrication of optical fibre long period gratings for CO₂ sensing - Barrington, James (Cranfield University, 2018)
This thesis investigated the repeatability of the overwrite long period grating (LPG) fabrication method and highlighted the advantage it offers in its ability to tune spectral features thus allowing the manufacture of bespoke sensors. Moreover, LPGs with periods ranging from 100 - 200 μm were written and a novel technique for mapping the transmission data was presented. This method gave a unique overview into the period mediated evolution of attenuation features, which, when designing LPGs that operate at the sensitive phase matching turning point, is invaluable. Further exploration into the overwrite method revealed that the UV irradiation duty cycle used in the fabrication of LPGs was found to influence the presence of harmonics, where a duty cycle of 25% maximised coupling to 2nd order transmission features. LPGs which possessed these additional spectral features within a small wavelength range (600 - 1000 nm) were assessed for their suitability in performing multi-parameter sensing. Ionic liquids were explored as an LPG COThis thesis investigated the repeatability of the overwrite long period grating (LPG) fabrication method and highlighted the advantage it offers in its ability to tune spectral features thus allowing the manufacture of bespoke sensors. Moreover, LPGs with periods ranging from 100 - 200 μm were written and a novel technique for mapping the transmission data was presented. This method gave a unique overview into the period mediated evolution of attenuation features, which, when designing LPGs that operate at the sensitive phase matching turning point, is invaluable. Further exploration into the overwrite method revealed that the UV irradiation duty cycle used in the fabrication of LPGs was found to influence the presence of harmonics, where a duty cycle of 25% maximised coupling to 2nd order transmission features. LPGs which possessed these additional spectral features within a small wavelength range (600 - 1000 nm) were assessed for their suitability in performing multi-parameter sensing. Ionic liquids were explored as an LPG COThis thesis investigated the repeatability of the overwrite long period grating (LPG) fabrication method and highlighted the advantage it offers in its ability to tune spectral features thus allowing the manufacture of bespoke sensors. Moreover, LPGs with periods ranging from 100 - 200 μm were written and a novel technique for mapping the transmission data was presented. This method gave a unique overview into the period mediated evolution of attenuation features, which, when designing LPGs that operate at the sensitive phase matching turning point, is invaluable. Further exploration into the overwrite method revealed that the UV irradiation duty cycle used in the fabrication of LPGs was found to influence the presence of harmonics, where a duty cycle of 25% maximised coupling to 2nd order transmission features. LPGs which possessed these additional spectral features within a small wavelength range (600 - 1000 nm) were assessed for their suitability in performing multi-parameter sensing. Ionic liquids were explored as an LPG CO₂ sensitive coating. It was shown that these materials demonstrate a refractive index change upon exposure to CO₂ which was maintained following mechanical stabilisation using a gelling agent. A coating system for applying the gelled ionic liquid to the surface of an optical fibre was developed and techniques to improve the coating deposition were explored. The sensor demonstrated an 8 nm wavelength shift in response to 20% CO₂, which was reversible by reducing the partial pressure of CO₂ for 25 min.sensitive coating. It was shown that these materials demonstrate a refractive index change upon exposure to CO₂ which was maintained following mechanical stabilisation using a gelling agent. A coating system for applying the gelled ionic liquid to the surface of an optical fibre was developed and techniques to improve the coating deposition were explored. The sensor demonstrated an 8 nm wavelength shift in response to 20% CO₂, which was reversible by reducing the partial pressure of CO₂ for 25 min. sensitive coating. It was shown that these materials demonstrate a refractive index change upon exposure to CO₂ which was maintained following mechanical stabilisation using a gelling agent. A coating system for applying the gelled ionic liquid to the surface of an optical fibre was developed and techniques to improve the coating deposition were explored. The sensor demonstrated an 8 nm wavelength shift in response to 20% CO₂, which was reversible by reducing the partial pressure of CO₂ for 25 min.